Crossing the Virtual Partition: Changing Jewish Rituals in Women’s Narratives - Gasztold, Brygida (Romanica Silesiana)
For many years excluded and marginalized, Jewish women have managed to alter the definitions of Jewish ritual in an attempt to find more self‑conscious ways of religious expression. My paper examines how literature reflects this process by demonstrating different strategies employed by women writers to bridge the gap created by androcentric narratives. Given the example of two novels: E.M. Broner’s A Weave of Women (1978) and Allegra Goodman’s Paradise Park (2001), I discuss the changing role of Jewish women in Judaism. Whether by mirroring the male rituals, or reshaping the existing foundations of Jewish practice and thought, they have managed to change the performance and conceptualization of modern Judaism; the process, which is by no means completed. Key words: Judaism, ritual, Jewish women, American‑Jewish literature